Expression of gap junction proteins connexins 26, 30, and 43 in Dupuytren's disease. (February 2014) - Holzer, Lukas A; Cör, Andrej; Holzer, Gerold
<x xml:space="preserve">Abstract</x> Background and purpose Dupuytren's disease (DD) is a benign fibroproliferative process of the palmar aponeurosis showing similarities to wound healing. Communication of cells involved in wound healing is mediated by the composition of gap junction (GJ) proteins. We investigated the expression of 3 GJ proteins, connexins 26, 30, and 43 (Cx26, Cx30, and Cx43) in DD. Patients and methods Fragments of Dupuytren's tissue from 31 patients (mean age 56 (30–76) years, 24 male) were analyzed immunohistochemically and compared to control tissue for expression of the GJ proteins Cx26, Cx30, and Cx43 and also alfa-smooth muscle actin (α-SMA). Results 14 of 31 samples could be attributed to the involutional phase (α-SMA positive) whereas 17 samples had to be considered cords in the residual phase (α-SMA negative). Expression of Cx26 and Cx43 was seen in 12 of the 14 samples from the involutional phase, and Cx30 was seen in 7 of these. Only 4 of the 17 samples from the residual phase showed any Cx, and there was none in the controls. Interpretation The high expression of GJ proteins Cx26, Cx30, and Cx43 in α-SMA positive myofibroblast-rich nodules, which are characteristic of the active involutional phase of DD, suggests that connexins could be a novel treatment target for the treatment of DD.